2021
DOI: 10.3389/fmicb.2020.555293
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Efficacy of Curcumin vs. Metformin in Modulating the Gut Microbiota in NAFLD Rats: A Comparative Study

Abstract: Structural disruption of gut microbiota is closely related to the occurrence of non-alcoholic fatty liver disease (NAFLD). Previous research has demonstrated that both curcumin (CUR) and metformin (MET) have a therapeutic effect against NAFLD and play a role in modulating the gut microbiota. However, there is a lack of direct comparison between the two medications in terms of the therapeutic efficacy and the regulatory effect on gut microbiota. In this study, we administered either CUR or MET to rats with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 49 publications
(56 reference statements)
5
20
0
Order By: Relevance
“…In our study, Barnesiella abundance is negatively correlated with hepatic TG content, suggesting that it may alleviate liver lipid deposition by regulating immune function. Similar to the previous study on rats, increased Romboutsia abundance induced by high-fat diets promoted liver lipid deposition and steatosis [ 33 ]. A recent study found that Ruminococcus_torques_group may be a key intestinal bacterium in promoting lipid deposition in poultry.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, Barnesiella abundance is negatively correlated with hepatic TG content, suggesting that it may alleviate liver lipid deposition by regulating immune function. Similar to the previous study on rats, increased Romboutsia abundance induced by high-fat diets promoted liver lipid deposition and steatosis [ 33 ]. A recent study found that Ruminococcus_torques_group may be a key intestinal bacterium in promoting lipid deposition in poultry.…”
Section: Discussionsupporting
confidence: 85%
“…It has antioxidant, anti-inflammatory, and anti-diabetic properties which should mitigate age-associated diseases [11][12][13]. Its basic mechanism of action as an anti-diabetic therapeutic agent was largely unknown [13][14][15][16][17][18]. However, we previously demonstrated that curcumin supplementation increases insulin sensitivity in hepatocytes by upregulating hepatic IDE expression and preserved islet integrity in a diet-induced obese (DIO) mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that increases in IL-1β, TNF-α and IL-6 play a key role in the pathogenesis of scleritis and that biological agents such as antitumor necrosis factor agents and interleukin-1 and interleukin-6 inhibitors control scleral inflammation either in an idiopathic manner or in a background of immune-mediated systemic disorders ( Sota et al, 2021 ). Romboutsia and Turicibacter are positively related to IL-6, IL-1β, TNF-α, IL-23 and IFN-γ ( Bosshard et al, 2002 ; Munyaka et al, 2016 ; Li et al, 2020 ). These cytokines can lead to an increase in macrophages and B cells, which are important in the pathogenesis of scleritis ( Nishio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%